Ricostruzione Digitale 3D del Palazzo del Vescovado: dal Medioevo a oggi .: Oggi Museo Diocesiano di arte sacra a Feltre (BL ). Ricostruzione storico-architettonica - Digital, Tre (Archeomatica, 2023)
3D digital reconstruction of the Palazzo del Vescovado di Feltre according to a historical, archaeological and architectural reconstruction. From the twin towers that overlooked Feltre to the reconstruction of the Palazzo del Vescovado up to the current Diocesan Museum of Sacred Art. The studio of the Arch. Gloria Manera was involved in the historical analysis of the building components, tracing each element back to the respective construction period wall by wall, dating it with accurate precision. These indications were reported on some CAD technical drawings and it was precisely the awareness that the two-dimensional representations were not sufficient to give consistency to the stratigraphic study that led to the choice of developing it on video, reconstructing the interventions that had taken place on the building. With the historical documents it was possible to advance their dating and chronology and using 3D animation software, Tre.digital objectively returns the various conformations of the building. The first phase of the project was research in the historical-artistic field by professionals, to then begin the phase of surveying the state of the building. According to experts and researchers, before the bishop's palace, there already existed two towers or strongholds, which stood out above the rocky massif of Feltre: an ideal and sheltered place to set up the new episcopal structure. Once the site was acquired, the first interventions on the structure, by Bishop Villalta, were to erect a solid retaining wall on the edge of the hill, while to the north the two towers were connected with a high wall. Subsequently the main entrance was protected with new structures.